2002
DOI: 10.1038/sj.mp.4001125
|View full text |Cite
|
Sign up to set email alerts
|

Transmission disequilibrium testing of arginine vasopressin receptor 1A (AVPR1A) polymorphisms in autism

Abstract: Impairment in social reciprocity is a central component of autism. In preclinical studies, arginine vasopressin (AVP) has been shown to increase a range of social behaviors, including affiliation and attachment, via the V 1a receptor (AVPR1A) in the brain. Both the behavioral effects of AVP and the neural distribution of the V1a receptor vary greatly across mammalian species. This difference in regional receptor expression as well as differences in social behavior may result from a highly variable repetitive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
191
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(208 citation statements)
references
References 21 publications
15
191
1
1
Order By: Relevance
“…The present study confirms and extends two previous investigations 6,7 showing association between the AVPR1a gene and autism. Kim et al 6 observed transmission disequilibrium between the RS1 and 115 autism trios and not with the second promoter region microsatellite RS3.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study confirms and extends two previous investigations 6,7 showing association between the AVPR1a gene and autism. Kim et al 6 observed transmission disequilibrium between the RS1 and 115 autism trios and not with the second promoter region microsatellite RS3.…”
Section: Discussionsupporting
confidence: 93%
“…For RS1, nine alleles (308-340) were identified and the distribution of allele frequencies is similar to previous reports. 6,7 For RS3, 16 alleles (318-350 bp) were identified and the distribution of allele frequencies is similar to a previous report. 5 …”
Section: Participantssupporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, SNPs associated with ASD are also associated with amygdala volume [29], depression/anxiety [29], negative emotionality [30], attention deficit [31], adult attachment styles [32,33] (but see [34]), affectivity, emotional loneliness and IQ [35], empathy and stress reactivity [36], observed parenting [37], with sexual phenotypes [38] and in our own studies with prosocial behavior [39]. Interestingly, the AVPR1a receptor of the closely related nonapeptide vasopressin has also been associated with ASD [40][41][42]. This provisional role of OT in ASD, is further supported by two linkage studies [43,44], clinical evidence by several groups demonstrating clinical improvement in ASD following OT administration [45][46][47][48][49][50][51] (also see [52,53]) and studies showing that ASD is also associated with alterations in OT plasma levels [54].…”
Section: Oxytocin and Autism Spectrum Disorders (Asd)mentioning
confidence: 58%
“…Our results support previous reports of the importance of the AVP system in these behaviors and may have clinical relevance to the understanding and treatment of similar corresponding disorders in humans. Autism, with its hallmark disturbances in social behavior, has been associated with polymorphisms in the V1aR gene (Kim et al, 2002), suggesting that modulation of this receptor and the AVP system may provide novel therapeutic targets for psychiatric disorders associated with social impairment, such as autism, as well as affective disorders such as anxiety disorder. However, the therapeutic potential of AVP treatment must not be overstated.…”
Section: Discussionmentioning
confidence: 99%